Students' Perception of the Campus Environment in the Context of Urban Morphology: A Case Study at Gorontalo State University in Gorontalo Urban Area - Irwan Wunarlan (International Journal of Technology and Education Research, 2026)
This study aims to analyze the influence of campus environment and urban morphology on students' perceptions in understanding spatial dynamics and learning comfort in the urban area of Gorontalo. A quantitative approach was used involving 172 respondents from Gorontalo State University. Data were collected through a survey with a Likert scale and analyzed using multiple linear regression to test the influence of campus environment (X₁) and urban morphology (X₂) variables on student perception (Y). The results of the analysis showed that the two independent variables had a positive and significant effect on student perception. The regression equation obtained Y = 1.645 + 0.208X₁ + 0.556X₂ with a simultaneous significance value (F-test) < 0.001, showing that the campus environment and urban morphology together affect student perception. The classical assumption test also showed that normality was fulfilled, there was no multicollinearity (VIF < 10), and heteroscedasticity was not detected. These findings show that the quality of campus physical space that is in sync with the morphological characteristics of the city can form a more positive, contextual, and reflective learning experience for students. This study recommends the importance of campus planning based on urban morphology and spatial interaction to strengthen the quality of the higher education environment in urban areas.